The Influence of Environmental, Social, And Governance (ESG) On Asset Quality in the Banking Industry - Aulia Busono; Titik Mildawati; Kurnia Kurnia (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the impact of Environmental, Social, and Governance (ESG) adoption on asset quality in Indonesian banks between 2019 and 2022. The Non-Performing Loan (NPL) ratio measures asset quality, while control variables include bank size, operating efficiency (BOPO), liquidity (LDR), capital structure (equity to total assets), economic growth (ΔGDP), and inflation. Conventional banks that are listed on the Indonesia Stock Exchange and regularly release sustainability and annual reports make up the sample. Panel data regression analysis results show that ESG considerably reduces non-performing loans (NPLs), indicating that stronger ESG regulations improve asset quality and reduce credit risk. Equity to Total Assets and BOPO also significantly influence asset quality, while other variables show no significant effects. These findings support Stakeholder Theory and Risk Management Theory by demonstrating that ESG functions as a governance and risk management mechanism that enhances banking stability. This research broadens our understanding of sustainable finance and offers useful advice for bank management and regulators looking to improve ESG implementation.